Analysis of Lifeboat Maintenance to Support Crew Safety on Board MV. Aliyah Pratama in Accordance with SOLAS Chapter III - Navire Tsabitah Lamaya; Damoyanto Purba; Elly Kusumawati; I'ie Suwondo (Journal of Engineering Science and Technology Management (JES-TM), 2026)
Non-compliance in the execution of lifeboat maintenance procedures significantly heightens operational risks and impairs evacuation effectiveness during maritime emergencies. This study evaluates the conformity of lifeboat maintenance and operational readiness on board the bulk carrier MV. Aliyah Pratama against the specific requirements of the Safety of Life at Sea (SOLAS) Chapter III Regulation 20 and the Life-Saving Appliances (LSA) Code. Utilizing a qualitative descriptive case study approach, data were collected over a 12-month period at Cilegon Anchorage through direct field observations, structured interviews with three key deck officers, and systematic reviews of the ship’s Planned Maintenance System (PMS) documentation. A compliance matrix was developed to benchmark observed mechanical and operational conditions against regulatory standards. The findings reveal critical discrepancies, including mechanical stiffness in the starboard gear brake, active corrosion on wire falls and winches, hardened watertight door seals, and expired emergency rations. Furthermore, abandon-ship drills demonstrated a lack of situational awareness and muster list comprehension among the crew. Root cause analysis, structured via the Ishikawa (Fishbone) framework, indicates that these non-conformities stem from superficial, visually limited inspections, high operational workloads, an aggressive saline environment, and shore-based procurement delays. The study concludes that the vessel's current maintenance execution functions primarily as an administrative formality rather than a rigorous functional safeguard. Corrective recommendations prioritize the implementation of deep-technical functional testing, expedited supply-chain logistics for safety equipment, and mandatory pre-drill tactical briefings to restore optimal evacuation.